Monitoring of Dust Devil Tracks Around the InSight Landing Site, Mars, and Comparison With In Situ Atmospheric Data. Issue 10 (16th May 2020) - Perrin, C.; Rodriguez, S.; Jacob, A.; Lucas, A.; Spiga, A.; Murdoch, N.; Lorenz, R.; Daubar, I. J.; Pan, L.; Kawamura, T.; Lognonné, P.; Banfield, D.; et al.
Abstract: The NASA InSight mission on Mars is a unique opportunity to study atmospheric processes both from orbit and in situ observations. We use post‐landing high‐resolution satellite images to monitor dust devil activity during the first 8 months of the mission. We perform mapping and semiautomatic detection of newly formed dust devil tracks and analyze their characteristics (sizes, azimuths, distances, and directions of motion). We find a large number of tracks appearing shortly after landing, followed by a significant decrease of activity during late winter, then a progressive increase during early spring. New tracks are characterized by dark linear, to slightly curvilinear, traces ranging from a few to more than 10 m wide. Tracks are oriented in the ambient wind direction, according to measurements made by InSight's meteorological sensors. The systematic analysis of dust devil tracks is useful to have a better understanding of atmospheric and aeolian activity around InSight. Plain Language Summary: The NASA InSight mission landed on Mars in November 2018. It carries weather and seismic stations that are now working continuously. We are also able to observe the InSight region from orbit using high‐resolution satellite images that have been acquired regularly over the first year of the InSight mission. They show a lot of dark traces on the surface, which are caused by whirlwinds called dust devils raising dust into the air. This phenomenon is not observed at the same rate over the entire year, as it depends on atmospheric conditions that vary with season. Our study with satellite images allows us to understand the characteristics of dust devil tracks and compare them with related measurements from the weather station on board InSight. These two sets of observations are well correlated to each other and provide significant constraints to better characterize the atmospheric activity around InSight and in the region of Elysium Planitia, Mars. Key Points: Many fresh linear and dark tracks caused by dust devils are detected from orbit near the InSight landing site Dust devil track formation rate decreases in late northern winter then increases in early spring Dust devil tracks' azimuths are in good agreement with InSight wind direction measurements